WATER-SOLUBLE SYNTHETIC POLYMERS IN MEDICAL APPLICATIONS - Mustafaeva, Zeynep (INST CATALYST & INORGANIC CHEMISTRY, 2016)
In this review, physiologically active polymers and impact of polyelectrolytes on the immunological parameters have been explored. Results obtained with addition of synthetic biopolymers show a higher protection against viral and bacterial infections which indicates a great potential for production of biotechnological vaccines. In this article the structure of polyelectrolytes is compared with natural polymers.
Keywords: biopolymers; polymeric adjuvants; polymers in vaccine formulations; AMPHIPHILIC IMMUNOGENS; POLYACRYLIC-ACID; SERUM-ALBUMIN; COMPLEXES; POLYELECTROLYTES; Chemistry